PENGARUH WAKTU PENYIMPANAN TERHADAP NILAI SUHU, KELEMBABAN DAN KESEGARAN SAYURAN PADA KEMASAN DAUN PISANG - Fuadi, Nurul; Astuti, Nini; Hernawati, Hernawati (JFT : Jurnal Fisika dan Terapannya, 2019)
This study was to determine the effect of storage time on temperature, humidity and freshness of vegetables on different packages. This research was carried out by packing green mustard vegetables, fruit tomatoes, and potato fruit using banana leaves and charcoal and without packaging using a thermohygrometer to measure temperature and humidity. Data retrieval is done once a day at 09.00 WITA to complete. The results of this study indicate that there is an effect of storage time on the value of temperature, humidity and freshness of vegetables. The freshness of green mustard vegetables lasts longer with banana leaf packaging than those using charcoal and without packaging. Freshness for fruit tomatoes and curly tomatoes lasts longer on the packaging of banana leaves that use charcoal than without packaging and which use banana leaf packaging. old without packaging compared to packaging and charcoal.